The Effect of Reward and Punishment on Learning Motivation in Physical Education Learning - Rahayu Prasetiyo; Arsika Yunarta (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
background: One of the learning barriers that occur in students is low learning outcomes and lack of student motivation to learn. Someone will change his behavior if he feels happy or not happy. One element of reinforcement (strengthening) is to provide rewards and punishments. Purpose: In this study the aim was to determine learning motivation that was influenced by reward and punishment. Reward in this study is in the form of values, while punishment is in the form of assignments Methods. The research method used is experimental research (Pretest–Posttest Control Group Design). The sample technique used is Cluster Random Sampling. The samples taken were 32 students of class VIII A and 32 students of class VIII B of SMP NEGERI 1 Jombang. Results and discussioin: Based on the results of data analysis using the SPSS data program, it can be seen that tcount with equal variances assumed (assuming both variances are the same or using the pooled variances test) is 2.341 with a probability of 0.023. Because the probability is <0.05, H0 is rejected, which means that the two sample means are different. In the sense that the average post-test of the experimental group is higher than the average value of the post-test of the control group. Thus that there is an influence of reward and punishment on learning motivation in learning physical education. Conclusion and Implications: In order to get better learning motivation, especially in giving reward and punishment, this learning method should be applied in learning physical education according to the abilities and conditions of students. Giving reward and punishment is used as a reference to increase student motivation. Limitation and recommendation: In this study is still limited to the provision of reward and punishment. In future research, it is better to examine the types or forms of reward and punishment that are effective on student learning motivation.